2014
DOI: 10.5812/ircmj.19118
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Therapeutic Effects of Garlic Tablet and Oral Metronidazole on Bacterial Vaginosis: A Randomized Controlled Clinical Trial

Abstract: Background:Bacterial vaginosis (BV) is one of the most common gynecological infections during reproductive age. Although metronidazole is one of the most effective medications recommended as the first-line treatment, it has various side effects. Because of the side effects and contraindications of some chemical medicines, using herbs has been investigated in treating BV.Objectives:The aim of this study was to compare the effect of garlic tablet (Garsin) and oral metronidazole in clinical treatment of the BV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…One of the earliest reports on this topic dates back from 1991, when Blackwell described the first therapeutic success of using plants extracts to treat BV (Blackwell, 1991 ). Subsequently, several clinical trials have demonstrated that the use of plant-derived compounds promoted the reduction of BV symptoms and are associated with high cure rates and tolerability, including a polyherbal vaginal pessary (Patel et al, 2008 ), vaginal cream containing Zataria multiflora (Abdali et al, 2015 ), a vaginal douche of thymol and eugenol (main constituents of thyme oil and clove oil; Sosto et al, 2011 ), watery extract of Triticum vulgare (Boselli et al, 2012 ) and garlic tablets (Mohammadzadeh et al, 2014 ). Surprisingly, up to now only one study evaluated the capability of plant-derived compound to eradicate BV biofilms.…”
Section: Emerging Therapeutic Alternatives Against Bvmentioning
confidence: 99%
“…One of the earliest reports on this topic dates back from 1991, when Blackwell described the first therapeutic success of using plants extracts to treat BV (Blackwell, 1991 ). Subsequently, several clinical trials have demonstrated that the use of plant-derived compounds promoted the reduction of BV symptoms and are associated with high cure rates and tolerability, including a polyherbal vaginal pessary (Patel et al, 2008 ), vaginal cream containing Zataria multiflora (Abdali et al, 2015 ), a vaginal douche of thymol and eugenol (main constituents of thyme oil and clove oil; Sosto et al, 2011 ), watery extract of Triticum vulgare (Boselli et al, 2012 ) and garlic tablets (Mohammadzadeh et al, 2014 ). Surprisingly, up to now only one study evaluated the capability of plant-derived compound to eradicate BV biofilms.…”
Section: Emerging Therapeutic Alternatives Against Bvmentioning
confidence: 99%
“…Garlic's antibacterial properties have been sparsely studied in the context of BV. One single-blinded study ( n = 120) found that oral garlic tablets and oral metronidazole have similar effectiveness in treating BV ( 114 ); however, the study was underpowered and did not adhere to CONSORT guidelines for reporting. No other studies have examined garlic intake in the context of BV.…”
Section: Complementary and Alternative Optionsmentioning
confidence: 99%
“…Evaluation at 7 to 10 days after beginning treatment found that treatment with garlic was as effective as treatment with metronidazole (63.3% and 48.3%, respectively; P = .141). The garlic group experienced more nausea and heartburn, but the metronidazole group experienced more vomiting, diarrhea, and headache …”
Section: Use Of Cam For Bvmentioning
confidence: 99%